Perspectives on Byzantine Archaeology - Castrorao Barba, Angelo; Castiglia, Gabriele (Brepols, 2022)
From the rule of Justinian (AD 527-AD 565) up to the Islamic conquests in the Byzantine Empire, the lands of the Mediterranean basin underwent significant change from the sixth to the ninth centuries AD. Urban and rural areas were transformed, landscapes altered, and material cultures saw a fundamental shift. But such changes were by no means uniform across the region. From Jordan, Greece, and the Danube, to the Italian peninsula, Sicily, Spain, and the Horn of Africa, the contributions gathered together in this volume explore new advances and perspectives from the field of ‘Byzantine’ archaeology over the <span class=